The athletes` visuomotor system - Cortical processes contributing to faster visuomotor reactions - Hülsdünker, T.; Strüder, H. K.; Mierau, A. (European Journal of Sport Science, 2018)
Many sports require athletes to rapidly transform visual information into a targeted motor response, a process referred to as visuomotor reaction. On the behavioural level, athletes have long been established to achieve faster simple visuomotor reaction times when compared to non-athletes. However, although the superior performance in athletes has been attributed to the central nervous system, the underlying neural mechanisms remained poorly studied. More recently, a growing number of neurophysiological and neuroimaging studies systematically addressed the functional and structural modulations in the athletes` visual and motor systems as well as their contribution to visuomotor performance. This article reviews current research on structural and functional characteristics of the athletes` cortical visuomotor system associated with simple visuomotor reactions, sports-specific visuomotor performance and visuomotor training. The primary objective is to shed light on the neural mechanisms potentially contributing to superior visuomotor reaction performance in athletes participating in visuomotor demanding disciplines. A more comprehensive understanding of performance-determining neural functions could provide great potential for diagnostics and training to improve athletic performance.